Uncovered equity parity: an empirical analysis for the Brazilian financial market - Zapp, Jan-Frederik (2018)
This paper analyzes if the uncovered equity parity conditions, established by Hau and Rey (2006), hold for Brazil or if divergent capital flow dynamics are observable. The paper applies a vector autoregressive model, capturing the interdependencies between local equity returns, capital flows, and currency returns. Contrary to Hau and Rey (2006), I find a positive relation between local equity returns and currency returns caused by the positive impact of local equity return shocks on foreign net capital flows. The results are in line with previous findings from emerging markets in Asia (Fuertes et al. (2017)).